Reimagining Gender through Picture Books: A Butlerian Reading of Three Children’s Narratives - Fatimah, Citra; Ruisah (Morphosis: Journal of Literature, 2025)
This study investigates the subversion of gender stereotypes in three contemporary children’s picture books: Franny’s Father is a Feminist (2018) by Rhonda Leet, Mary Wears What She Wants (2019) by Keith Negley, and My Shadow is Purple (2022) by Scott Stuart. Anchored in Judith Butler’s (1990) theory of gender performativity, the research examines how these texts portray and challenge traditional gender norms. Employing a qualitative descriptive method, the study analyzes both narrative structures and visual representations to uncover how gender identities are constructed, performed, and disrupted within each story. The findings demonstrate that the selected books effectively resist binary conceptions of gender by presenting characters who confront, reject, and redefine societal expectations. Each narrative offers a distinct yet cohesive model of gender subversion—whether through feminist parenting, sartorial defiance, or non-binary self-expression—ultimately encouraging young readers to embrace diversity, autonomy, and equality. This study highlights the critical role of children’s literature in shaping gender awareness from an early age and underscores the potential of picture books as tools for promoting inclusivity and challenging normative discourses. The research contributes to ongoing scholarly conversations on gender, identity, and pedagogy in children’s literature and calls for further exploration into the impact of such texts in diverse educational and cultural contexts.